The effect of the mindfulness-based transition to motherhood program in pregnant women with preterm premature rupture of membranes. Issue 7 (3rd July 2017) - Korukcu, Oznur; Kukulu, Kamile
ABSTRACT: The purpose of the researchers is to determine the effect of a mindfulness program on readiness for motherhood, the level of maternal attachment, and on postpartum self-evaluation. We used a quasiexperimental design. Researchers applied the mindfulness-based Transition to Motherhood program to the treatment group for 7 days. Data were collected between December 2012 and June 2014 in Turkey. At the end of the study, the treatment group showed improvement in measures of acceptance of pregnancy, level of readiness to give birth, level of maternal attachment, and level of competence in the role of motherhood.